2016
DOI: 10.1016/j.wjorl.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological study of surgical margins in squamous cell carcinoma of buccal mucosa

Abstract: ObjectiveTo evaluate the margins of resected specimen of oral squamous cell carcinoma (SCC) and to document the surgical margin (measured at the time of resection) and margins at the time of pathological examination (after immersion of the specimen in formalin).MethodsPatients who were diagnosed and confirmed with squamous carcinoma of buccal mucosa were included in the study. Patients underwent resection of the tumor with a margin of 1 cm. Soon after resection, the distance between outermost visible margin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…It has been suggested that adequate resection of OCSCC requires at least 5‐mm margins, although smaller margins have also been suggested . Because of the complexity of these tumors, clear margins are achieved in only 50% to 80% of patients treated at cancer centers . Hence, many patients with early OCSCC undergo inadequate surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that adequate resection of OCSCC requires at least 5‐mm margins, although smaller margins have also been suggested . Because of the complexity of these tumors, clear margins are achieved in only 50% to 80% of patients treated at cancer centers . Hence, many patients with early OCSCC undergo inadequate surgery.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Because of the complexity of these tumors, clear margins are achieved in only 50% to 80% of patients treated at cancer centers. [8][9][10][11][12] Hence, many patients with early OCSCC undergo inadequate surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Our nomogram indicates that pathological grade is the most important factor, while age is the second most important one [15,16], and there is no signi cant difference between grades I and II. Multivariate analyses indicated that older age was an independent risk variable, with older patients having a lower survival rate [9,17,18]. Meanwhile, a higher AJCC stage was associated with worse survival [9].…”
Section: Discussionmentioning
confidence: 98%
“…Among the three main treatments applied in BSCC, surgery was found to be the only signi cantly effective treatment, and so the radiotherapy and chemotherapy statuses were not included in the nal nomogram. Surgical treatment should be the rst choice of treatment for BSCC [18,20,21], while avoiding unnecessary radiotherapy and chemotherapy can reduce the burden on medical resources, alleviate the additional injury and pain experienced by patients, and reduce costs. This information can further help clinicians to make rational clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical plan should involve wide excision of the tumor in all three dimensions with adequate margins ( Table 2). This should account for histopathological shrinkage (approximately 25%) [2]. Due attention must be given specially to the third dimension which is the soft tissue/depth and generally the site of surgical failures.…”
Section: Management Of Primary Lesionmentioning
confidence: 99%